Empowering youth: the value of Krajicek peer leaders on playgrounds in underserved Dutch neighborhoods - Gioia N. Muru; Tessa A. ten Tije; Dorine C. M. Collard; Joske Nauta; Femke van Nassau (International Journal of Adolescence and Youth)
This study investigates the role of Krajicek Peer Leaders (KPLs), young people aged 15–27 who organize activities on playgrounds in underserved neighbourhoods in the Netherlands. The aim of this study was to explore the requirements in selecting KPLs, their collaboration with local stakeholders, and the unique contributions they bring to both the Krajicek Playgrounds and their own development. A mixed-method approach was used including questionnaires, interviews and informal conversations across four stakeholder groups. Results revealed varying requirements and recruitment processes to become a KPL. Collaboration between neighbourhood sports coaches and KPLs was found generally positive; KPLs offer additional capacity, foster social safety, and serve as role models for children at the playground. KPLs experience personal growth through skills development and increased confidence. This study underscores the broader benefits of deploying young peer leaders, showcasing the added value for both the playground and for the young people themselves.